2003
DOI: 10.1037/1089-2699.7.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Effects of member mood states on creative performance in temporary workgroups.

Abstract: Previous individual-level research suggests that positive mood promotes creative problem solving (A. M. Isen, 2000). The current study built on these results to investigate group-level phenomena. Temporary workgroups (N ϭ 57) were induced to experience positive, neutral, or negative mood before engaging in a creative production task. The results indicated that positive mood increased creative performance and implementation efficiency, whereas negative mood had no effect. Regarding group process, positive and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
134
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(146 citation statements)
references
References 38 publications
8
134
1
3
Order By: Relevance
“…Research has, accordingly, demonstrated positive affect to enhance task performance behavior and organizational citizenship behavior both at the individual (Kaplan, Bradley, Luchman, & Haynes, 2009;Tsai, Chen, & Liu, 2007) and at the group level (George, 1996;Grawitch, Munz, & Kramer, 2003). Transferring these findings to the organizational level of analysis, "broaden-and-build theory predicts that positive emotions in organizational settings not only produce individuals who function at higher levels, but may also produce organizations that function at higher levels" (Fredrickson, 2003, p. 174).…”
Section: Tfl Climate and Organizations' Positive Affective Climatementioning
confidence: 92%
“…Research has, accordingly, demonstrated positive affect to enhance task performance behavior and organizational citizenship behavior both at the individual (Kaplan, Bradley, Luchman, & Haynes, 2009;Tsai, Chen, & Liu, 2007) and at the group level (George, 1996;Grawitch, Munz, & Kramer, 2003). Transferring these findings to the organizational level of analysis, "broaden-and-build theory predicts that positive emotions in organizational settings not only produce individuals who function at higher levels, but may also produce organizations that function at higher levels" (Fredrickson, 2003, p. 174).…”
Section: Tfl Climate and Organizations' Positive Affective Climatementioning
confidence: 92%
“…Specifically, the moods and emotions group members experience are reciprocally related to both their thought processes and behaviors. In fact, based on George's (1990) theorizing that affect may be a meaningful construct at the group level of analysis, research has focused on understanding the antecedents and consequences of group affective tone (e.g., Bartel Downloaded by ["Queen's University Libraries, Kingston"] at 12:56 18 September 2013& Saavedra, 2000George, 1995;Grawitch, Munz, Elliot, & Mathis, 2003;Grawitch, Munz, & Kramer, 2003;Mason & Griffin, 2003;Totterdell, Kellett, Teuchmann, & Briner, 1998), defined as relatively consistent or homogeneous affective reactions within a group. An implicit, and at times explicit, assumption in the literature on group affective tone is that a positive affective tone is functional for groups and their members (George & King, 2007).…”
Section: Group Processesmentioning
confidence: 99%
“…In jobs where creativity is an asset, the evidence also suggests that positive affect can enhance originality and flexibility (Estrada, Isen, & Young, 1994;Grawitch, Munz, Elliott, & Mathis, 2003;Grawitch, Munz, & Kramer, 2003;Isen, Daubman, & Nowicki, 1987;Isen, Johnson, Mertz, & Robinson, 1985; for nonexperimental work, see Madjar, Oldham, & Pratt, 2002). For example, physicians in a positive mood were able to solve problems more creatively than their neutral mood counterparts (Estrada et al, 1994).…”
Section: Experimental Evidence: Does Happiness Lead To Success In Thementioning
confidence: 99%